2009
DOI: 10.1378/chest.08-1233
|View full text |Cite
|
Sign up to set email alerts
|

Achieved Anticoagulation vs Prosthesis Selection for Mitral Mechanical Valve Replacement

Abstract: Background: Thromboembolic events (TEs) are frequent after mechanical mitral valve replacement (MVR), but their association to anticoagulation quality is unclear and has never been studied in a population-based setting with patients who have a complete anticoagulation record. Conclusion: This population-based comprehensive study of anticoagulation and TE post-MVR shows that, in these closely anticoagulated patients, anticoagulation intensity was highly variable and not associated with TE incidence post-MVR. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“… 7 , 15 , 33–35 The acute risk for valve thrombosis or thromboembolism even in timely anticoagulated patients amounts up to 1% per day for valve thrombosis and 0.2% per day for systemic thromboembolisms including ischaemic stroke and is greatest immediately after surgical implantation. 36 , 37 In line with these data, we here noticed a thromboembolism rate of 0.2% per day in anticoagulated patients, and in patients without anticoagulation there was a rather modestly increased rate of 0.6% per day. Now, comparing incidence rates of haemorrhagic complications we documented a 10 times higher hazard with early anticoagulation.…”
Section: Discussionsupporting
confidence: 89%
“… 7 , 15 , 33–35 The acute risk for valve thrombosis or thromboembolism even in timely anticoagulated patients amounts up to 1% per day for valve thrombosis and 0.2% per day for systemic thromboembolisms including ischaemic stroke and is greatest immediately after surgical implantation. 36 , 37 In line with these data, we here noticed a thromboembolism rate of 0.2% per day in anticoagulated patients, and in patients without anticoagulation there was a rather modestly increased rate of 0.6% per day. Now, comparing incidence rates of haemorrhagic complications we documented a 10 times higher hazard with early anticoagulation.…”
Section: Discussionsupporting
confidence: 89%
“…The risk of thromboembolism is highest in the first 3 months after prosthetic heart valve replacement or repair, with a risk of 3.6% to 10%, declining to \4% after 90 days. 10,11 Whenever possible, elective procedures should be delayed for at least 3 months after valve surgery. 12 Based on the 2006 American College of Cardiology / American Heart Association valvular disease guidelines, the 2012 European Society of Cardiology valvular guidelines, and the 2012 American College of Chest Physicians guidelines, the presence of any one of the following features, in the setting of a prosthetic heart valve, places patients at high risk for thromboembolism: atrial fibrillation, prior thromboembolism, left ventricular ejection fraction \35%, mitral or tricuspid valve placement, 2 prosthetic valves, or older aortic ball or tilting disc valves.…”
Section: Assessment Of Thromboembolic Riskmentioning
confidence: 99%
“…Ten studies (n = 93,448) reported 13 evaluations on the relationship between malignancy and major or any bleeding (15,21,23,26,(29)(30)(31)(36)(37)(38). No study reported such a relationship with minor bleeding.…”
Section: Malignancymentioning
confidence: 99%